Penerapan Akad Ijarah Muntahiya Bittamlik (IMBT) Di Bank Syariah - Hastriana, Anna Zakiyah; Imaniyah, Helwatin (Jurnal Landraad, 2024)
Sharia banking in Indonesia has experienced a significant increase in performance, as evidenced by the proliferation of Islamic financial institutions. The ijarah (rent) contract, which is frequently utilized in daily life, is one of the fascinating contracts to talk about. Human needs cause constant adjustments to this agreement. The contract ijarah muntahiya bittamlik (IMBT), sometimes referred to as al-Ijarah thumma al-bai' (AITAB), and hire and buy are two examples of such modifications. This agreement uses two separate contracts, namely a lease contract (ijarah / leasing or renting) and a sale and purchase contract (bai '/ purchase). IMBT contracts are comparable to the traditional lease agreements that are still in use today. The author finds that the IMBT contract can be a solution in providing affordable Public Housing Loans to the public, Yet, because of the dearth of research and practical understanding surrounding the contract, it is still sporadically utilized in Islamic banking.